2020
DOI: 10.1021/acs.estlett.0c00754
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Organic Aerosol from Typical Chinese Domestic Cooking Emissions

Abstract: Cooking has been proven to be a significant source of primary organic aerosol, especially in megacities. However, the formation of secondary organic aerosol (SOA) derived from cooking emissions is still poorly understood. In this work, four prevalent Chinese domestic cooking types involving complicated cuisines and various cooking methods were chosen to conduct a lab simulation for SOA formation using a Gothenburg potential aerosol mass reactor (Go: PAM). After samples had been aged under OH exposures of 4.3−2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 68 publications
3
28
0
Order By: Relevance
“…Unfortunately, the SOA factor corresponding to other POA (likely biomass burning OA) has not been resolved. Some studies have found that OA emitted by biomass burning will be rapidly oxidized in the ambient atmosphere, and the BBOA in the fresh plume is mostly aged OA (Zhou et al, 2017). When the aged biomass burning OA is further oxidized, it is difficult to identify the biomass burning SOA from mixed within OOA without constraining its SOA factor.…”
Section: Application Of Established Poa and Soa Profile In Ambient Oa Source Apportionmentmentioning
confidence: 99%
“…Unfortunately, the SOA factor corresponding to other POA (likely biomass burning OA) has not been resolved. Some studies have found that OA emitted by biomass burning will be rapidly oxidized in the ambient atmosphere, and the BBOA in the fresh plume is mostly aged OA (Zhou et al, 2017). When the aged biomass burning OA is further oxidized, it is difficult to identify the biomass burning SOA from mixed within OOA without constraining its SOA factor.…”
Section: Application Of Established Poa and Soa Profile In Ambient Oa Source Apportionmentmentioning
confidence: 99%
“…The alcohol/peroxide pathway can produce a less oxidized oxygenated organic aerosol (Z. Zhang et al, 2020). Additionally, polycyclic aromatic hydrocarbons (PAHs) induce negative impacts during gene expression via entry into cells and production of either intermediate or final metabolites (Dey et al, 2021;Mehmood et al, 2020).…”
mentioning
confidence: 99%
“…Furthermore, we have attempted to apply the laboratory mass spectra from this work to the ambient air. The contributions of vehicle SOAs and cooking SOAs to OAs were estimated by an ME-2 model in urban Beijing (Zhang et al, 2021). It was found that cooking SOAs (27 %-42 % of OAs) and vehicle SOAs (58 %-73 % of OAs) presented different diurnal patterns, implying their different formation pathways.…”
Section: Discussionmentioning
confidence: 99%